2012
DOI: 10.2134/jeq2011.0462
|View full text |Cite
|
Sign up to set email alerts
|

Biosulfides Precipitation in Weathered Tailings Amended with Food Waste-based Compost and Zeolite

Abstract: Tailings are mine wastes in the form of slurries stacked in mine sites abandoned after the exhaustion of ores. There are approximately 5000 abandoned mine sites in Korea, and tailings have become a serious environmental problem. Long‐term environmental exposure of tailings can cause release of acidic and high concentrations of sulfate‐ and metal‐contaminated water (acid mine drainage, AMD). Organic and/or inorganic amendments have been studied for AMD prevention and passive in situ treatment of pore water. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…The leaching solution of Coal Gangue 1-3 was neutral or weak alkaline, and the leaching solution of Coal Gangue 4 was acidic. Neutral pH can promote SRB growth [32], accelerate the metabolic activity of SRB, increase pH and reduce ORP. In the second stage, the average pH values of the effluent from the 4 columns were 7.93, 7.86, 9.09 and 8.02, and the average ORP value were −204.33 mV, −236.92 mV, −262.83 mV and −112.83 mV, respectively.…”
Section: Dynamic Leaching Experiments Results Of Four Kinds Of Coal Gamentioning
confidence: 99%
“…The leaching solution of Coal Gangue 1-3 was neutral or weak alkaline, and the leaching solution of Coal Gangue 4 was acidic. Neutral pH can promote SRB growth [32], accelerate the metabolic activity of SRB, increase pH and reduce ORP. In the second stage, the average pH values of the effluent from the 4 columns were 7.93, 7.86, 9.09 and 8.02, and the average ORP value were −204.33 mV, −236.92 mV, −262.83 mV and −112.83 mV, respectively.…”
Section: Dynamic Leaching Experiments Results Of Four Kinds Of Coal Gamentioning
confidence: 99%
“…At 35 °C, the pH value increases most obviously, mainly because SRB has high growth activity and large reproduction quantity at this temperature, so the alkalinity generated by metabolism is large. At the same time, the alkaline pH value of the solution further promotes the growth and metabolism of SRB …”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the alkaline pH value of the solution further promotes the growth and metabolism of SRB. 27 It can be seen from Figure 2c that the ORP values under different culture temperatures decreased significantly with the extension of culture time. After 8 days of incubation, the ORP values of the solution were −297, −371, −393, −128, and −102 mV, respectively.…”
Section: Growth Curve Of Srbmentioning
confidence: 96%
“…Hao T. [21] found the sulfate reduction process is accompanied by organic carbon mineralization, bicarbonate production and, subsequently, an increase in pH and alkalinity. At the same time, bagasse and medical stone absorbed the free H+ by electrostatic adsorption, so the pH of the effluent was stable in the neutral range, which can provide favorable growth conditions for SRB [22] and promote the growth of SRB. Studies have shown that the composite minerals such as quartz and feldspar in the medical stone [23] have a strong regulatory effect on acidic pH.…”
Section: Analysis Of the Change Of Ph And Oxidation Reduction Potentimentioning
confidence: 99%